Listen to the silent night - Mackall, Dandi Daley; Johnson, Steve, 1960-; Fancher, Lou. (New York : Dutton Childrens Books, 2011)
Rhyming text reveals many sounds heard on the night of Jesus' birth, such as the flapping of Joseph's sandals as he walks into Bethlehem, the lowing of a cow in the stable, and the flutter of angels' wings as they proclaim the news.
Keywords: Jesus Christ -- Nativity -- Fiction; Stories in rhyme; Sound -- Fiction; Noise -- Fiction